Efficacy of a Modified Live Porcine Reproductive and Respiratory Syndrome Virus 1 (PRRSV-1) Vaccine against Experimental Infection with PRRSV AUT15-33 in Weaned Piglets - Sophie Duerlinger; Christian Knecht; Spencer Sawyer; Gyula Balka; Marianne Zaruba; Till Ruemenapf; Christian Kraft; Poul Henning Rathkjen; Andrea Ladinig (Vaccines, 2022)
In this study, the efficacy of the commercial modified live PRRSV-1 vaccine “Ingelvac PRRSFLEX® EU” was assessed in weaned piglets experimentally infected with PRRSV strain AUT15-33. Seventy-four weaned piglets were allocated to five groups. Vaccinated (groups 1, 2, and 5) and non-vaccinated piglets (groups 3 and 4), infected with either a low dose (103 TCID50/dose; groups 2 and 4) or a high dose (105 TCID50/dose; groups 1 and 3) of the virus, were compared regarding clinical signs, average daily weight gain (ADG), lung lesions, viral load in serum, oral swabs, and tissue samples. In comparison to vaccinated animals, coughing increased notably in the second week after challenge in non-vaccinated piglets. During the same time period, vaccinated, high-dose-infected piglets showed significantly higher ADG (p < 0.05) than non-vaccinated, high-dose-infected animals. All infected piglets reached approximately the same viremia levels, but vaccinated animals showed both a significantly reduced viral load in oral fluid (p < 0.05) and tissue samples and significantly reduced lung lesions (p < 0.05). In conclusion, vaccination was able to increase ADG, reduce the amount of viral shedding via oral fluids, and reduce the severity of lung lesions and the viral load in tissue samples under experimental conditions.